Higher BMI is associated with stronger effects of social cues on everyday snacking behaviour. (1st July 2017) - Schüz, Benjamin; Revell, Sarah; Hills, Andrew P.; Schüz, Natalie; Ferguson, Stuart G.
Abstract: Discretionary food choices (snacks) contribute up to a third of the daily energy intake and potentially contribute to energy imbalance and weight gain. Individual snack intake behaviour is guided by internal and external cues, with social cues (seeing others eat, being alone) consistently showing large effects. A wide body of (mainly laboratory-based) research suggests marked differences in people's response to eating cues based on BMI. Here, we show that these BMI differences in cue responsiveness also pertain to everyday snacking behaviour. In two combined ecological momentary assessment studies, 122 participants with BMIs ranging from 18.34 to 45.71 kg/m 2 logged their everyday snacking behaviour in real-time over two weeks along with the presence or absence of social cues. Random-effects modelling showed that people with higher BMI were more likely to consume high-energy snacks when alone, and were more likely to consume low-energy snacks in the presence of others eating. This suggests BMI differences in cue responsiveness that are in line with impression management theory and underlines the importance of social cues for snacking behaviour and provides avenues for both theory and intervention development.